Effectiveness of a Multi-Component Intervention for Overweight and Obese Children (Nereu Program): A Randomized Controlled Trial. - Noemi Serra-Paya; Assumpta Ensenyat; Iván Castro-Viñuales; Jordi Real; Xènia Sinfreu-Bergués; Amalia Zapata; Jose María Mur; Gisela Galindo-Ortego; Eduard Solé-Mir; Concepció Teixido (PLoS ONE, 2015)
Introduction Treatment of childhood obesity is a complex challenge for primary health care professionals. Objectives To evaluate the effectiveness of the Nereu Program in improving anthropometric parameters, physical activity and sedentary behaviours, and dietary intake. Methods Randomized, controlled, multicentre clinical trial comparing Nereu Program and usual counselling group interventions in primary care settings. The 8-month study recruited 113 children aged 6 to 12 years with overweight/obesity. Before recruitment, eligible participants were randomly allocated to an intensive, family-based multi-component behavioural intervention (Nereu Program group) or usual advice from their paediatrician on healthy eating and physical activity. Anthropometric parameters, objectively measured sedentary and physical activity behaviours, and dietary intake were evaluated pre- and post-intervention. Results At the end of the study period, both groups achieved a similar decrease in body mass index (BMIsd) compared to baseline. Nereu Program participants (n = 54) showed greater increases in moderate-intense physical activity (+6.27% vs. -0.61%, p<0.001) and daily fruit servings (+0.62 vs. +0.13, p<0.026), and decreased daily soft drinks consumption (-0.26 vs. -0.02, p<0.047), respectively, compared to the counselling group (n = 59). Conclusions At the end of the 8-month intervention, participants in the Nereu Program group showed improvement in physical activity and dietary behaviours, compared to the counselling group. Trial registration ClinicalTrials.gov NCT01878994.